(3MGTjI Ydi GdJUQjas - (3eMeO Hf bGSe GdYQHjs ((3eMeO s)
(3ChdgG (B:s
(3bGd eMeO Hf bGSe GdYQHi hHYO agPG JYdjb dWja Ydi TQM GdJUQja jaJM eZdbg bhdg HSe Gddg GdQMef GdQMje s
(3BNQgG (B:s
(3Ci GdJJHY deG LGAJg GdCHhGH GdKGdKI GdJi PcQhgG ai ZjQgG JeJ GdJYdjbI GddWjaI PGJ GdJMbjbGJ GddWjaI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs